El divorcio de mutuo consentimiento ante el notario y su incidencia en la liquidación de los bienes de la sociedad conyugal - Pérez Zamora, Katherine Alexandra (2015)
This work of legal research, I made in order to reform Article Art. 18 Paragraph 22 of the Notary Law, to forewarn the rights of children who suffer the consequences of divorce of their parents, delaying the clearance of goods conjugal, which can lead to children affected by divorce their parents. It is structured in six chapters. The main part, to the knowledge of the problem and the effect it was necessary to hypothesize that the solution to the problem was on the reform of Art. 18 Paragraph 22 of the Notary Law. In the theoretical framework, we refer to aspects: Historical, Doctrinal and Legal. The methodology used in the investigation we can emphasize the methods used, the types of research, people, samples of techniques and instruments used in data collection